Hubungan Durasi Paparan Fume Pengelasan dan Penggunaan Masker Las Terhadap Fungsi Paru pada Pekerja Las Pt. X Kota Batam Tahun 2026 - Alya Angel; Trisna Dewita; Hening Rizky Permata (Jurnal Ragam Pengabdian, 2026)
Exposure to welding fumes is a risk factor for impaired lung function commonly found among welders in the shipbuilding industry. This study aims to determine the relationship between the duration of exposure to welding fumes and the use of welding masks on lung function among welders at PT. X in Batam City in 2026. This study is an analytical observational study using a cross-sectional approach. The population consists of welders at PT. X in Batam City, with a sample size of 40 respondents. The research instruments included a questionnaire, an observation sheet, and spirometry tests, with the results analyzed using the Chi-Square test. The results showed a significant association between the duration of welding fume exposure and lung function (p < 0.001) and between the use of welding masks and lung function (p < 0.001). Workers with an exposure duration of >8 hours/day exhibited abnormal lung function in 72.2% of cases, whereas all workers using masks in the “good” category had normal lung function (100%). It is concluded that both variables are significantly associated with the lung function of welding workers. Companies are advised to consistently require the use of NIOSH-standard masks and to limit working hours in accordance with applicable regulations.